Varying Cognitive Scars – Differential Associations Between Types of Childhood Maltreatment and Facial Emotion Processing - Iffland, Benjamin; Neuner, Frank (Frontiers in Psychology, 2020)
Background: Distorted cognitive processing has been found among survivors of child maltreatment. However, different types of abuse and neglect may bring about differences in emotion and attention processing. The present study aimed to detect differential associations between various types of childhood maltreatment and attentional biases in facial emotion processing. Methods: A non-clinical sample was recruited on University campus and consisted of 67 individuals with varying degrees of maltreatment. In an evaluative conditioning task, images of faces with neutral emotional expressions were either associated with short videos of intense negative statements, or associated with neutral videos. Subsequently, these faces were used as stimuli in a face in the crowd recognition task in which the familiar faces had to be recognized within a crowd of unfamiliar neutral faces. Results: In multiple linear regression analyses controlling for the intercorrelatedness of types of maltreatment, differential relationships between types of maltreatment and attentional bias were found. While emotional abuse was associated with faster detection of negatively associated faces, emotional neglect was associated with an impaired recognition of familiar stimuli regardless of the emotional content. Conclusions: Results indicated that interindividual differences in cognitive biases may be due to the activation of diverse cognitive schemas based on differential experiences of maltreatment.